Denta care in ICU patients: A literature review on the association of the most common diseases caused by poor oral hygiene and the importance of the dentist in prevention (Research, Society and Development, 2022)
Hospital Dentistry is the practice that cares for and prevents oral changes in patients who are hospitalized in Intensive Care Units (ICU) by multidisciplinary teams. Periodontal diseases (PD) are infectious, asymptomatic and chronic, which occur from the exposure of the host to the action of bacteria that settle on the teeth, which may be gingivitis, periodontitis, or another systemic disease, such as Nosocomial Pneumonia (PN) an acute infection of the lungs, related to poor hygiene of the oral cavity, considered the second most common infection in hospitalized patients. The care by dental surgeons (CD) in (ICU) has as main purpose the prevention of oral infections, which can interfere in the evolution of the pathologies installed in the hospitalized patient. In this sense, the article aims to review the integrative literature, seeking to associate periodontal and systemic diseases with the importance of the Dental Surgeon in ICUs. To guide the research, databases were consulted: Google Scholar, SciELO, Pubmed and Lilacs, using the descriptors: “preventive dentistry”, “hospital dentistry”, “dental care in the ICU”, “oral diseases acquired in the ICU”; in Portuguese and English, from 2000 to 2021. The study made it possible to understand that the CD is indispensable in the care of patients affected with both PD and PN. It is concluded that the CD can act on infections of the oral cavity and respiratory tract, controlling microorganisms that colonize the mouth, in adequate hygiene and in medication action, providing a better quality of life for the patient.